Bridge vehicle load model on different grades of roads in China based on Weigh-in-Motion (WIM) data. (July 2018) - Chen, Bin; Ye, Ze-nan; Chen, Zengshun; Xie, Xu
Highlights: The traffic composition and the variation over time on four grades of road in China were explored. Statistical models of speed, axle weight, and gross vehicle weight were established. A fatigue load model of vehicles was established based on a two-stage method. Abstract: Bridge vehicle load is an important parameter that is relevant to the construction and maintenance stages of a bridge. In recent years, a large number of orthotropic steel deck bridges have been built in China, and it is urgent to establish a fatigue load model that reflects the actual traffic conditions of the bridges. This study has investigated the variation of vehicles over time on four grades of road (expressway, first-class highway, second-class highway and urban main road) according to the weight-in-motion (WIM) data. Subsequently, the statistical model was established in terms of speed, axle weight, and gross weight of vehicle (GVW) acting on the four grades of road. Finally, a fatigue load model of vehicles on the four grades of road was established based on a two-stage method. The results show that (1) the speed of vehicle on the four grades of road obeys the unimodal distribution; (2) the GVW of two- and three-axle vehicles on the four grades of road belongs to the t -distribution and the log-normal distribution, respectively; (3) the GVW of four- and five-axle vehicles on expressways is a finite mixed distribution, whereas the GVW of four- and five-axle vehicles on the remain three grades of road obeys the log-logistic and log-normal distribution respectively; (4) the GVW of six- and above axle vehicles on expressways and second-class highways obeys a finite mixed distribution with two variables, whereas that on first-class and urban main roads obeys the log-normal distribution; (5) the axle weight of standard fatigue vehicles differs remarkably on different grades of roads, which is difficult to describe the fatigue damage in a uniform standard fatigue vehicle.